PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI JAMUR KELAS X SMA - Yosi Amanda Arif Amanda Arif; Darmawati '; Wan Syafi’i Syafi'i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research was to develop the Student Worksheet based on scientific approach to improve students' critical thinking on fungi content for grade X High Schoo. The reaserch was done at Faculty of Education, University of Riau in January until May 2015. The study refers to research approaches Research and Development using ADDIE models developed by Dick and Carry. Research carried out until the stage of development. The subjects is KD 3.6 senior high school grade X in fungi content that had been developed into five student worksheet. Data was collected using a validation sheet filled out by 5 validators and limited trial aimed at high school students who have studied in fungi content. Population and samples for limited trial randomly determined that the class X MIA 4 in SMA Negeri 1 Pekanbaru as many as 20 students. Results of the validation of the design, pedagogical and content aspects showed all student worksheets obtain an average score of 3.53, 3.66, 3.62, 3.69 and 3.68 categorized as very valid while the limited test results from the aspect of design, pedagogy and content showed all student worksheet obtain an average score 3.58, 3.58, 3.61, 3.58 and 3.61 with the excellent category. Keywords: Development, Student Worksheet, Scientific Approach, Critical Thinking